Clotrimazole Drug Resistance in Candida glabrata Clinical Isolates Correlates with Increased Expression of the Drug:H+ Antiporters CgAqr1, CgTpo1_1, CgTpo3, and CgQdr2 - Costa, Catarina; Ribeiro, Jonathan; Miranda, Isabel M.; Silva-Dias, Ana; Cavalheiro, Mafalda; Costa-de-Oliveira, Sofia; Rodrigues, Acácio G.; Teixeira, Miguel C. (Frontiers in Microbiology, 2016)
For years, antifungal drug resistance in Candida species has been associated to the expression of ATP-Binding Cassette (ABC) multidrug transporters. More recently, a few drug efflux pumps from the Drug:H+ Antiporter (DHA) family have also been shown to play a role in this process, although to date only the C. albicans Mdr1 transporter has been demonstrated to be relevant in the clinical acquisition of antifungal drug resistance. This work provides evidence to suggest the involvement of the C. glabrata DHA transporters CgAqr1, CgQdr2, CgTpo1_1 and CgTpo3 in the clinical acquisition of clotrimazole drug resistance. A screening for azole drug resistance in 138 Candida glabrata clinical isolates, from patients attending two major Hospitals in Portugal, was performed. Based on this screening, ten clotrimazole susceptible and ten clotrimazole resistant isolates were selected for further analysis. The transcript levels of CgAQR1, CgQDR2, CgTPO1_1 and CgTPO3 were found to be significantly up-regulated in resistant isolates when compared to the susceptible ones, with a level of correlation that was found to be similar to that of CgCDR2, an ABC gene known to be involved in the clinical acquisition of resistance. As a proof-of-concept experiment, the CgTPO3 gene was deleted in an azole resistant C. glabrata isolate, exhibiting high levels of expression of this gene. The deletion of CgTPO3 in this isolate was found to lead to decreased resistance to clotrimazole and fluconazole, and increased accumulation of azole drugs, thus suggesting the involvement of this transporter in the manifestation of azole resistance.